Albania : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key findings of the fiscal transparency evaluation for Albania. Many of the fundamental elements of fiscal transparency are now in place. The budget clearly shows the government's forecasts of revenue and its plans for spending and for financing the deficit. The budget is detailed, showing spending on each of several hundred government programs. Reports on the implementation of the budget are frequent, timely, and comprehensive. Basic data on revenue and spending are published monthly, usually no more than 20 days after the end of the month. Quarterly and annual reports give more detailed information. There are even daily reports listing each government payment.